Die Geburt der Lebensphilosophie aus dem Geist der Konfliktsoziologie - Fitzi, Gregor (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2016)
The development of Simmel’s “life philosophy” characterizing the late phase of his work is ordinarily presented as the product of the reception of his contemporaries, above all Henri Bergson, whom he contributed to translate and introduce in Germany. The present essay shows, however, that Simmel’s life-forms paradigm has a completely different origin. It emerges from the essential core of Simmel’s theory of modern society, i.e. from his theory of social conflict. By showing that conflict is not simply a dividing factor but a process of sociation that integrates societies, Simmel realized that the epistemological dichotomy between process and substance had to be overcome in and open-ended conception of their dialectics going beyond Hegel’s teleological conception of historical development. Simmel found the semantics to express his conception in the examination of the life philosophy of his time, but he radically transformed it to point out the problem he wanted to address. To understand the particular nature of his question, it is important to trace its origins within his sociology.